On the Correlation between Algerian EFL Learners’ Critical Thinking Skill and Reading Ability - Boumaza, Hadjer; Grine, Nadia (Journal of Human Sciences, 2021)
The present work purports to study the relationship between critical thinking and reading ability among EFL learners in the Algerian context. Data for the study are collected from twenty-two master one students in the department of English at 8 Mai 1945 Guelma University, Algeria and seven teachers working at two Algerian universities: 8 Mai 1945 Guelma, and Badji Mokhtar Annaba. Instruments used to collect the data are; a critical thinking test, the IELTS (International English Language Testing System) reading test, semi-structured interviews and instant messages interviews. The nature of the relationship between EFL learners’ critical thinking level and reading ability is determined through the calculation of the correlation coefficient (r). It was revealed that there is a significant positive correlation between the study variables.